The Contributions of Memory and Vocabulary to Non-Verbal Ability Scores in Adolescents with Intellectual Disability - Mungkhetklang, Chantanee; Bavin, Edith L.; Crewther, Sheila G.; Goharpey, Nahal; Parsons, Carl (Frontiers in Psychiatry, 2016)
It is usually assumed that performance on nonverbal intelligence tests reflects visual cognitive processing and aspects of working memory will be involved. However the unique contribution of memory to nonverbal scores is not clear, and nor is the unique contribution of vocabulary. Thus we aimed to investigate these contributions. Nonverbal test scores for seventeen individuals with Intellectual Disability (ID) and thirty-nine children with Typical Development (TD) of similar mental age were compared to determine the unique contribution of visual and verbal Short-Term Memory (STM) and Working Memory (WM), and the additional variance contributed by vocabulary scores. No significant group differences were found in the nonverbal test scores or receptive vocabulary scores but there was a significant difference in expressive vocabulary. Regression analyses indicate that for the TD group STM and WM (both Visual and Verbal) contribute similar variance to the nonverbal scores. For the ID group, Visual STM and Verbal WM contributed most of the variance to the nonverbal test scores. The addition of vocabulary scores to the model contributed greater variance for both groups. More unique variance was contributed by vocabulary than memory for the TD group, whereas for the ID group memory contributed more than vocabulary. Visual and auditory memory and vocabulary contributed significantly to solving visual nonverbal problems for both the TD group and the ID groups. However for each group there were different weightings of these variables. Our findings indicate that for individuals with TD, vocabulary is the major factor in solving nonverbal problems, not memory, whereas for adolescents with ID, Visual STM and Verbal WM are more influential than vocabulary, suggesting different pathways to achieve solutions to nonverbal problems.